Biosensors and nanomaterials and their application for mycotoxin determination - Tothill, Ibtisam E. (Wageningen Academic Publishers, 2011)
Mycotoxin analysis and detection in food and drinks is vital for ensuring food quality and safety, eliminating and controlling the risk of consuming contaminated foods, and complying with the legislative limits set by food authorities worldwide. Most analysis of these toxins is still conducted using conventional methods; however, biosensor methods are currently being developed as screening tools for use in field analysis. Biosensors have demonstrated their ability to provide rapid, sensitive, robust and cost-effective quantitative methods for on-site testing. The development of biosensor devices for different mycotoxins has attracted much research interest in recent years with a range of devices being designed and reported in the scientific literature. However, with the advent of nanotechnology and its impact on the evolution of ultrasensitive devices, mycotoxin analysis is also benefiting from the advances taking place in applying nanomaterials in sensors development. This paper reviews the developments in the area of biosensors and their applications for mycotoxin analysis, as well as the development of micro/nanoarray transducers and nanoparticles and their use in the development of new rapid devices